The blue revolution: sustainable water management for a thirsty world - Amarachi Paschaline Onyena; Kabari Sam (Discover Sustainability)
Abstract The twenty-first century presents critical challenges to global water resources, with rising consumption, scarcity, and security issues threatening human well-being and ecosystem health. Regions such as the Middle East, North Africa, China, and the USA are already experiencing significant impacts on health, livelihoods, and ecosystems due to the global water crisis. By 2050, projections indicate that two billion people across 44 countries will face severe water scarcity, with over two billion currently lacking access to safe drinking water and 3.6 billion enduring annual shortages. Climate change, urbanization, and economic development further exacerbate these challenges, intensifying pressure on water systems and threatening biodiversity. This research synthesizes global data on water scarcity, examines case studies of successful interventions, and analyses key drivers of water scarcity stress to propose actionable strategies. The Blue Revolution Strategy offers a comprehensive model for sustainable water management, emphasizing efficient use, waste reduction, and ecological integration. Leveraging its principles -such as innovative water technologies, water-efficient agriculture, and community engagement; can help developing nations achieve sustainable water management. Results demonstrate that ecosystem-based approaches, combined with advanced technologies like membrane distillation and smart water systems, significantly enhance water use efficiency across sectors. Integrated and interdisciplinary strategies, involving collaboration among governments, businesses, and stakeholders, are essential to addressing future demands and overcoming socio-economic barriers to water access. The policy recommendations emphasize the importance of collaborative governance to ensure long-term environmental and social sustainability in water resource management.